Pengaruh Verbal Bullying terhadap Mental Interpersona Siswa di SDI Harekakae - Rosalinda Fatin; Marsela Luruk Bere; Marianus Teti; Yohana Febriana Tabun (Jurnal Pendidikan Dirgantara, 2025)
This study investigates the influence of verbal bullying on the interpersonal mental condition of students at SDI Harekakae. Verbal bullying refers to aggressive behavior involving harsh words, insults, or threats that may negatively affect a student’s psychological well-being. A quantitative method with a correlational design was used. The research involved 320 students selected through proportional random sampling. Instrument validity and reliability were confirmed, with a Cronbach’s Alpha value of 0.821, indicating strong consistency. Normality testing using the Shapiro-Wilk method showed that the data were normally distributed. Pearson correlation analysis showed a weak and statistically insignificant relationship (r = 0.143; p = 0.452) between verbal bullying and interpersonal mental condition. Although the t-test resulted in a p-value of 0.032, further interpretation indicated no significant effect of the independent variable on the dependent variable. These findings suggest that verbal bullying does not significantly affect students' interpersonal mental health and highlight the importance of further research to explore other contributing factors.